Sustainability Reporting dan Return Saham pada Perusahaan Terindeks IDXQ30 - Andriani, Ni Made Dina; Sudana, I Putu (E-Jurnal Akuntansi; Vol 33 No 9 (2023)DO - 10.24843/EJA.2023.v33.i09.p03, 2023)
The issuance of POJK NO.51/POJK.03/2017 resulted in companies having an obligation to prepare sustainability reporting. This research aims to determine the effect of sustainability reporting on stock returns of companies indexed by IDXQ30 in 2020-2021. The analytical method used is multiple linear regression analysis with a sample size of 46. In this research, the company's sustainability reporting is measured by the sustainability reporting disclosure index which refers to the GRI Standards. This research includes control variables for profitability, solvency and company size which aim to increase the statistical power of this research. The results of this research show that sustainability reporting has no effect on stock returns. Sustainability reporting is not yet information that has economic value for investors, so the information in sustainability reporting has not been used as a consideration in investing. Keywords: Sustainability reporting, GRI Standards, stock returns, IDXQ30